2022
DOI: 10.1155/2022/5046761
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of the Efficacy and Safety of Olanzapine versus Clozapine when Treating Senile Dementia

Abstract: Objective. To systematically assess the safety and efficacy of olanzapine versus clozapine when treating senile dementia and to provide evidence-based medicine basis for its promotion and use. Methods. PubMed, Embase, ScienceDirect, Cochrane Library, China Knowledge Network Database (CNKI), China VIP Database, Wanfang Database, and China Biomedical Literature Database (CBM) online database were searched for randomized controlled trials (RCT) of olanzapine and clozapine when treating senile dementia. The retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…36,49,[103][104][105][106]140 Although many are not approved for use in elderly patients with dementia in many countries, such as Switzerland, atypical antipsychotics have been shown to be effective in reducing psychotic symptoms and agitation. [110][111][112][113]115,[117][118][119][120][121][122] However, the risk-benefit ratio needs to be carefully assessed because of the various dangers to which they may expose patients, such as increased mortality and risk of stroke, or accelerated cognitive decline. 141 Risperidone is the atypical antipsychotic with the most published evidence in the literature, and its effects are supported by numerous RCTs (although the effect in RCTs is rather weak).…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…36,49,[103][104][105][106]140 Although many are not approved for use in elderly patients with dementia in many countries, such as Switzerland, atypical antipsychotics have been shown to be effective in reducing psychotic symptoms and agitation. [110][111][112][113]115,[117][118][119][120][121][122] However, the risk-benefit ratio needs to be carefully assessed because of the various dangers to which they may expose patients, such as increased mortality and risk of stroke, or accelerated cognitive decline. 141 Risperidone is the atypical antipsychotic with the most published evidence in the literature, and its effects are supported by numerous RCTs (although the effect in RCTs is rather weak).…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
“…Although many are not approved for use in elderly patients with dementia in many countries, such as Switzerland, atypical antipsychotics have been shown to be effective in reducing psychotic symptoms and agitation 110–113,115,117–122 . However, the risk–benefit ratio needs to be carefully assessed because of the various dangers to which they may expose patients, such as increased mortality and risk of stroke, or accelerated cognitive decline 141 .…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%